2019
DOI: 10.1017/ipo.2019.15
|View full text |Cite
|
Sign up to set email alerts
|

Constructive emotions? Patriotism as a predictor of civic activity in Poland

Abstract: In many post-communist countries, the concept of patriotism is used instrumentally in populist discourses. It is rarely the subject of a substantive public debate, in which symbolic elites would be able to openly discuss and negotiate the scope of its meaning in front of an interested audience. A long-term plan to shape constructive civil attitudes gives way to the pressure of being effective in current politics. The author proposes to look at the category of patriotism in a socially useful way and to treat it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 50 publications
2
9
0
1
Order By: Relevance
“…Among the factors that cause students not to be interested in volunteer activities are due to time management factors, fatigue, volunteer activities that are biased and involve only one race and there is not enough information about increasing the spirit of volunteerism in Malaysia in general and universities in particular. This is in line with a study conducted by Marzecki (2019) on Poland students. Although constructive patriotism is often associated with volunteering but the studies conducted failed to link constructive patriotism as a cause of making students active or participating in volunteering activities.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Among the factors that cause students not to be interested in volunteer activities are due to time management factors, fatigue, volunteer activities that are biased and involve only one race and there is not enough information about increasing the spirit of volunteerism in Malaysia in general and universities in particular. This is in line with a study conducted by Marzecki (2019) on Poland students. Although constructive patriotism is often associated with volunteering but the studies conducted failed to link constructive patriotism as a cause of making students active or participating in volunteering activities.…”
Section: Discussionsupporting
confidence: 93%
“…Druckman (1994) states whether a positive view of one's own country will cause us to view other countries from a purely negative angle. The findings of this study are in line with a study conducted by Marzecki (2019) which showed a significant relationship between patriotism with the formation of Poland students' identity. Patriotism helps in the formation of students' identity and in turn causes students to strive to show a good moral code to maintain the good name of the country.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The article by Marzęcki (2019) examines the category of patriotism from a social point of view, and also presents research data on the meaning of patriotism among Polish students. Gusacov (2018) notes that the upbringing of patriotism, it is love and fidelity of Motherland, it can be an educational solution for restoration and cohesion, as well as for building social solidarity between groups of Israel citizens and within them.…”
mentioning
confidence: 99%